(untitled) (XXI Century. Spanish Literature and Culture, 2020)
This paper aims at identifying various functions of “memory”, which constitutes a main theme in Julio Llamazares’ novel El Cielo de Madrid (2005). Recalling the past years that the protagonist spent as a youn man in Madrid, the author makes use of a great deal of devices to highlight the role of imagination and memory. Throughout the chapters of the novel, the author turns Madrid with its sky into a mythical (imaginative), yet a real, place.